An enhanced data mapping algorithm for two-level requests in WiMAX systems - Tsern-Huei Lee; Dinh-Dung Le; Yaw-Wen Kuo (TENCON ... IEEE Region Ten Conference, 2013)
The IEEE 802.16e standard, which adopts OFDMA PHY and is generally known as Mobile WiMAX, has grabbed the attention of wireless communication industry for the past few years. It is a technology optimized for IP-based high speed long-distance wireless broadband access. In the downlink of Mobile WiMAX systems, data requests have to be mapped into rectangular regions. Such a constraint results in an NP-complete problem in order to maximize throughput. Several heuristic data mapping algorithms were proposed trying to achieve high system throughput. Most of the algorithms handle only one type of data. In a previous paper, we presented a data mapping algorithm which maps two levels of requests, i.e., urgent and non-urgent data. However, only the numbers of required slots were considered in determining the order of data mapping. In this paper, we propose an enhanced version which considers both the number of required slots and the Modulation and Coding Scheme (MCS) for each mobile station. Simulation results show that, compared with previous design, the enhanced algorithm serves more urgent data with higher throughput.